Optimizing MSME Product Authenticity Verification Using Serverless Event-Driven Microservices on Hybrid Blockchain Architecture - Zulkarnain, Adnan; Yusuf, Roby Firnando (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2025)
The rapid proliferation of counterfeit products poses critical risks to Micro, Small, and Medium Enterprises (MSMEs), eroding consumer trust and hindering market competitiveness. This study proposes a Serverless Event-Driven Microservices Hybrid Blockchain Architecture to enable real-time, cost-efficient MSME product authentication. The architecture integrates Solana blockchain, leveraging its high throughput and low transaction fees, with AWS Lambda–based serverless microservices and Redis in-memory caching to enhance scalability and responsiveness. The system was empirically evaluated across transaction loads ranging from 1,000 to 100,000, measuring throughput, latency, scalability, and cost efficiency. Experimental results demonstrate that the proposed framework achieved up to 970 transactions per second (TPS) with average latency between 12 and 32 ms, while reducing operational costs by approximately 80 % compared with traditional monolithic systems. Statistical validation confirmed the reliability of performance gains (p < 0.001), and regression analysis (R² = 0.97) indicated near-linear scalability under increasing workloads. These findings substantiate the architectural advantages of combining serverless elasticity, event-driven orchestration, and hybrid blockchain consensus, resulting in a self-scaling, fault-tolerant verification platform suitable for MSME environments. The framework establishes an empirically grounded pathway for practical blockchain adoption in resource-constrained ecosystems and provides a foundation for future extensions involving edge computing, predictive caching, and cross-chain interoperability.